Kemajuan dan aplikasi superkonduktor modern berbasis silicon, germanium, karbon, dan 〖MgB〗_(2 ): tinjauan literatur terbaru - Saelillah, Mannanu Minni (Maliki Interdisciplinary Journal, 2025)
Superconductors are materials that exhibit zero electrical resistance and magnetic field expulsion (Meissner effect) below a critical temperature. These properties make them highly promising for future technologies, including lossless power transmission, energy-efficient electronics, and medical applications. This review focuses on four non-conventional superconductors: silicon, germanium, carbon, and magnesium diboride (MgB₂). The discussion highlights their physical properties, synthesis methods, and potential applications based on recent literature. References were collected from international databases using the keywords “superconductor,” “silicon,” “germanium,” “carbon-based superconductors,” and “MgB₂.” The findings show that MgB₂ exhibits the most stable performance with a transition temperature of about 39 K, while silicon and germanium require heavy doping or high pressure to display superconductivity. Carbon in the form of nanotubes and fullerenes demonstrates strong potential at the nanoscale. Despite challenges related to low transition temperatures and complex synthesis methods, all four materials show significant prospects for advancing superconducting applications in energy, electronics, and medicine